Income inequality in the UK: comparisons with five large Western European countries and the USA - Dorling, D (Elsevier, 2015)
This paper concentrates on the 1% richest households in the UK in a comparison with the other four large Western European countries: Germany, France, Italy and Spain. In the European context the UK is an outlier of extreme inequality. Individual level tax data has shown this previously, but earlier research did not make comparisons at the household level, or in as much detail as it is now possible to show now given new survey findings.